A complex genetic architecture underlies mandibular evolution in big mice from Gough Island. Issue 4 (7th February 2022) - Parmenter, Michelle D; Nelson, Jacob P; Gray, Melissa M; Weigel, Sara; Vinyard, Christopher J; Payseur, Bret A
Abstract: Some of the most compelling examples of morphological evolution come from island populations. Alterations in the size and shape of the mandible have been repeatedly observed in murid rodents following island colonization. Despite this pattern and the significance of the mandible for dietary adaptation, the genetic basis of island-mainland divergence in mandibular form remains uninvestigated. To fill this gap, we examined mandibular morphology in 609 F2s from a cross between Gough Island mice, the largest wild house mice on record, and mice from a mainland reference strain (WSB). Univariate genetic mapping identifies 3 quantitative trait loci (QTL) for relative length of the temporalis lever arm and 2 distinct QTL for relative condyle length, 2 traits expected to affect mandibular function that differ between Gough Island mice and WSB mice. Multivariate genetic mapping of coordinates from geometric morphometric analyses identifies 27 QTL contributing to overall mandibular shape. Quantitative trait loci show a complex mixture of modest, additive effects dispersed throughout the mandible, with landmarks including the coronoid process and the base of the ascending ramus frequently modulated by QTL. Additive effects of most shape quantitative trait loci do not align with island-mainland divergence, suggesting that directional selection played a limited role in the evolution of mandibular shape. In contrast, Gough Island mouse alleles at QTL for centroid size and QTL for jaw length increase these measures, suggesting selection led to larger mandibles, perhaps as a correlated response to the evolution of larger bodies. Abstract : Populations that colonize islands often evolve new phenotypes over short timescales. Parmenter et al . report that the largest wild house mice on record—mice from Gough Island—evolved divergent mandibular morphology through many small genetic steps. Effects of the quantitative trait loci discovered suggest that directional selection played a limited role in the evolution of mandibular shape, in contrast to size evolution.